(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article highlights the importance and necessity of creating permanent jobs based on the analysis of the number of registered, active, inactive, terminated and newly established enterprises and organizations, as well as the analysis of employed and unemployed people in the economy.